2007
DOI: 10.1111/j.1365-2559.2007.02619.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression of β‐catenin and p53 are prognostic factors in deep aggressive fibromatosis

Abstract: The overexpression of beta-catenin and p53 is associated with a decreased event-free survival in deep aggressive fibromatosis. Further studies are required to establish whether these findings can lead to an improvement in the treatment of this rare neoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
58
3
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 28 publications
1
58
3
2
Order By: Relevance
“…A recent publication indicates that desmoids exhibiting increased nuclear expression (defined as Ͼ20% of the tumor cells expressing ␤-catenin) had a significantly higher recurrence rate than desmoids lacking nuclear ␤-catenin expression. 49 In our study no correlation could be demonstrated between percentage of positive staining nuclear ␤-catenin tumor cells and desmoid recurrence and desmoids negative for ␤-catenin staining were very rare. However, it is intriguing that decreased rather than increased nuclear ␤-catenin staining intensity was significantly associated with a more aggressive disease phenotype in our study.…”
Section: Discussionmentioning
confidence: 41%
“…A recent publication indicates that desmoids exhibiting increased nuclear expression (defined as Ͼ20% of the tumor cells expressing ␤-catenin) had a significantly higher recurrence rate than desmoids lacking nuclear ␤-catenin expression. 49 In our study no correlation could be demonstrated between percentage of positive staining nuclear ␤-catenin tumor cells and desmoid recurrence and desmoids negative for ␤-catenin staining were very rare. However, it is intriguing that decreased rather than increased nuclear ␤-catenin staining intensity was significantly associated with a more aggressive disease phenotype in our study.…”
Section: Discussionmentioning
confidence: 41%
“…The estimated incidence in the general population is 2 -4/1,000,000/year. [11] No significant racial or ethnic distribution is reported. In children, a fibromatosis incidence of 2.2% is mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Vimentin Actin S100 Desmin Table 2 Immunohistochemical profiles of fibromatosis and other benign spindle cell lesions [11,12] 1. Surgery…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear β-catenin immunoreactivity is staining positive in 67%-80% of cases in the reported series, but staining for nuclear β-catenin is not specific for desmoids, since it is also observed in 56% of superficial fibromatosis, 30% of low-grade myofibroblastic sarcomas and 22% of solitary fibrous tumors (8,11,15,72,83,84). The IHC studies on hormone receptor status show 0 to 7.4% positivity for ER-α, 7.4% to 100% positive staining for ER-β, 0 to 25.5% for progesterone receptor-A (PR-A), 0 to 33.3% for progesterone receptor-B (PR-B) and 13 to 52.9% for androgene receptor (AR) (42,72,(83)(84)(85)(86)(87). The IHCs for epidermal growth factor receptor (EGFR), c-erbB2, c-KIT, CD34 were uniformly negative reported in the literature and, in general desmoids are regarded as ER-α and c-KIT negative tumors (83,84,85,(87)(88)(89)(90).…”
Section: Histologymentioning
confidence: 99%
“…The IHC studies on hormone receptor status show 0 to 7.4% positivity for ER-α, 7.4% to 100% positive staining for ER-β, 0 to 25.5% for progesterone receptor-A (PR-A), 0 to 33.3% for progesterone receptor-B (PR-B) and 13 to 52.9% for androgene receptor (AR) (42,72,(83)(84)(85)(86)(87). The IHCs for epidermal growth factor receptor (EGFR), c-erbB2, c-KIT, CD34 were uniformly negative reported in the literature and, in general desmoids are regarded as ER-α and c-KIT negative tumors (83,84,85,(87)(88)(89)(90).…”
Section: Histologymentioning
confidence: 99%